Profile of Dowry Death Cases Reported for Autopsy in Thoothukudi Medical College - A Retrospective Study - Seethalakshmi.M 1 , Rajalakshmi. S.2 , Rajesh.R3 , Vinoth K.V.4 , (Indian Journal of Forensic Medicine & Toxicology, 2020)
Violence against women inside the family is a worldwide phenomenon. Violence against women traversesevery geographical area, economic layers, education level, age, and employment status. It is seen that in spiteof its high education status and all around acclaimed social method of advancement, India is at top positionin Dowry Death. United Nation General Assembly in 1993 embraced the Declaration on the Elimination ofViolence against Women. All the medicolegal cases brought to an autopsy that is registered under section304 B IPC are included in this study. Inclusion criteria: Death of married women within 7 years of marriage.A total of 80 cases were analyzed retrospectively. 71(88.75%) cases belong to Hindu religion. 45(56.25%)cases are from urban regions, 40(50%) cases completed high school education, 44 (55%) of the deathsoccurred in 2-4 years of marriage, 63(78.75%) cases belong to arranged marriage, 32(40%) cases belongedto nuclear family, 65 (75%)cases belong to the age group 18 to 25 years, 3(3.75%) cases were homicide,Hanging is the most common form of death in this study 44(55%) cases. The government of India hasattempted to battle the developing rate of dowry death by instituting different laws to keep such deaths fromhappening and to punish those responsible when they do happen. Notwithstanding lawful forward leaps,stunning news on dowry deaths kept on appearing in Indian papers